A Study of Artificial Intelligence Education System and Traditional Education System - Bhari, Purushottam Lal; CD, Kumawat (International Journal of Computer Sciences and Engineering, 2019)
Application and usage of Artificial intelligence is increasing day by day in almost every arena. Therefore, education system has also offered a big platform for execution of intelligence technologies in it. A survey has been conducted on educational environment to understand the importance of different educational methods. In this analysis, 218 faculties of different disciplines from different colleges/universities and from different areas have been included. This research paper is an endeavor to compare and analyze artificial intelligence based educational environment and traditional environment using some common issues of teaching and learning.